Why aren't British sprinters faster? - Cleather, D. J. (New Studies in Athletics, 2017)
Great Britain and Northern Ireland (GBR) has a wealth of talented U20 sprinters, which in the last 15 years has been second to only the USA and comparable with other strong sprinting nations like Jamaica and Nigeria. However, the development of the best British U20 sprinters during their senior careers tends to lag behind and the average personal best 100m times for GBR's top 20 senior men and women are notably slower than for the athletes from the other countries mentioned. This study based on publically available data shows that British men experience less improvement between the ages of 20 and 23 years, whereas British women improve less from 23 years to their career end. This results in relatively slower career personal bests that are achieved at a younger age. After discussing possible explanations in detail, the author concludes that coaches and support personnel working with sprinters in Great Britain and Northern Ireland should critically appraise their practices (in comparison to the development pathways of more successful nations) in order to improve the development of the next generation of British sprinters.